Preoperative glasgow prognostic score was an effective prognostic indicator in patients with biliary tract cancer - Rongqiang Liu; Ling Wang; Jing Ye; Xinyi Li; Wangbin Ma; Ximing Xu; Jia Yu; Weixing Wang (Frontiers in Immunology)
BackgroundThe Glasgow Prognostic Score (GPS) is a well-established prognostic indicator that effectively reflects the inflammatory, nutritional, and immune status of cancer patients. GPS has been shown to be associated with survival outcomes in many different cancers. However, its prognostic significance in biliary tract cancer (BTC) remains unclear. This meta-analysis aims to explore the prognostic value of GPS in BTC patients.MethodsA systematic search was conducted in PubMed, Embase, and Web of Science to identify relevant studies. Survival data including overall survival (OS), disease-free survival (DFS) and recurrence-free survival (RFS) were the main observation indicators. Hazard ratios (HRs) with 95% confidence intervals (CIs) were extracted and pooled for meta-analysis.ResultsA total of 16 articles incorporating 1919 patients were included in the study. High GPS was associated with poor OS (HR:2.00, 95% CI:1.62-2.48) and DFS/RFS (HR:2.50, 95% CI:1.71-3.65). Subgroup analysis further confirmed the prognosis value of GPS in BTC patients.ConclusionsGPS could serves as a valuable prognostic marker in BTC patients and may aid in risk stratification and treatment decision-making.